MODERASI BERAGAMA DALAM MIMBAR GEREJA: PENDEKATAN INKLUSIF DAN KONTEKSTUAL - Yeremia Hia; Elfin Warnius Waruwu (Sekolah Tinggi Teologi Arastamar Bengkulu, 2025)
This research investigates the practice of religious moderation in church pulpits, focusing on the implementation of moderation values in daily religious life. Through a qualitative approach with a literature study that explores information through books and articles that discuss this topic to understand how religious moderation is realized in teaching, preaching, and other religious activities. In-depth observations with church leaders and congregation members, as well as participatory observation, provided deep insights into their perspectives and experiences of religious moderation. This research also aims to identify the main challenges faced by churches in practicing moderation and contribute to the literature related to the importance of religious moderation in places of worship. Through this approach, the authors provide a holistic and in-depth understanding of the practice of religious moderation in church pulpits and contribute to the development of strategies and policies that support religious moderation in the church environment and society at large.